Tracing banks' credit allocation to their funding costs - Anne Duquerroy; Adrien Matray; Farzad Saidi (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We quantify how banks' funding costs affect their lending behavior directly, and indirectly by feeding back to their net worth. For identification, we exploit banks' heterogeneous liability structure and the existence of regulated deposits in France whose rates are set by the government. Using administrative credit-registry and regulatory bank data, we find that a one-percentage-point increase in funding costs reduces credit by 17%. To insulate their profits, banks reach for yield and rebalance their lending towards smaller and riskier firms. These changes are not compensated for by less affected banks at the aggregate city level, with repercussions for firms' investment.
Keywords: E23; E32; E44; G20; G21; L14; 330; bank funding costs; monetary-policy transmission; deposits; credit supply; SMEs; saving